Materials and characterization techniques for high-temperature polymer electrolyte membrane fuel cells - Zeis, Roswitha (Beilstein Journal of Nanotechnology, 2015)
The performance of high-temperature polymer electrolyte membrane fuel cells (HT-PEMFC) is critically dependent on the selection of materials and optimization of individual components. A conventional high-temperature membrane electrode assembly (HT-MEA) primarily consists of a polybenzimidazole (PBI)-type membrane containing phosphoric acid and two gas diffusion electrodes (GDE), the anode and the cathode, attached to the two surfaces of the membrane. This review article provides a survey on the materials implemented in state-of-the-art HT-MEAs. These materials must meet extremely demanding requirements because of the severe operating conditions of HT-PEMFCs. They need to be electrochemically and thermally stable in highly acidic environment. The polymer membranes should exhibit high proton conductivity in low-hydration and even anhydrous states. Of special concern for phosphoric-acid-doped PBI-type membranes is the acid loss and management during operation. The slow oxygen reduction reaction in HT-PEMFCs remains a challenge. Phosphoric acid tends to adsorb onto the surface of the platinum catalyst and therefore hampers the reaction kinetics. Additionally, the binder material plays a key role in regulating the hydrophobicity and hydrophilicity of the catalyst layer. Subsequently, the binder controls the electrode–membrane interface that establishes the triple phase boundary between proton conductive electrolyte, electron conductive catalyst, and reactant gases. Moreover, the elevated operating temperatures promote carbon corrosion and therefore degrade the integrity of the catalyst support. These are only some examples how materials properties affect the stability and performance of HT-PEMFCs. For this reason, materials characterization techniques for HT-PEMFCs, either in situ or ex situ, are highly beneficial. Significant progress has recently been made in this field, which enables us to gain a better understanding of underlying processes occurring during fuel cell operation. Various novel tools for characterizing and diagnosing HT-PEMFCs and key components are presented in this review, including FTIR and Raman spectroscopy, confocal Raman microscopy, synchrotron X-ray imaging, X-ray microtomography, and atomic force microscopy.
Keywords: binder; catalysts; characterization techniques; high-temperature polymer electrolyte membrane fuel cell (HT-PEMFC); membrane electrode assembly (MEA); phosphoric acid-doped polybenzimidazole (PBI)